DESIGN METHOD FOR STRONG COLUMNS-WEAK BEAMS FOR RISK CATEGORY IV BUILDINGS WITH TIME HISTORY PERFORMANCE ANALYSIS - P Adi Yasa; Made Hendra Prayoga; Ida Bagus Prastha Bhisama (Universitas Udayana, 2024)
Collapse pattern that considers the design of strong columns-weak beams in structures located in areas prone to large earthquakes such as Indonesia is an important thing that must be considered. When a large earthquake occurs in buildings with risk category IV based on SNI 1726-2019, the flexible parts of the beam elements are allowed to experience damage, while the columns must not experience soft-story mechanisms. To obtain a more realistic picture of it, in this study Nonlinear Time History Analysis (NLTHA) was chosen because it is considered able to provide a picture of the structural behavior that is closer to reality than Pushover Analysis. The results of the 2D time history performance analysis indicate that a beam-column capacity ratio of 1.2, as specified in SNI 2847-2019, renders the structure unable to achieve the expected collapse performance. By using a trial-and-error process to obtain a safe collapse hierarchy, an increase in column capacity of 2 to 3 times the SNI 2847-2019 column design is obtained. Based on this, in designing structures with risk category IV, apart from having to meet the terms and conditions of SNI the structure also needs to be analyzed for its performance using a more realistic methods such as NLTHA (portal) or 3D to ascertain whether the planned failure pattern can occur or not. This is important considering that the beam column capacity ratio in SNI is not sufficient to reach the Collapse Prevention (CP) condition of 95%.